Peranan Orangtua dalam Meningkatkan Motivasi Belajar Anak di PAUD Salikussibyan Dusun Kelotok Desa Wakan Kecamatan Jerowaru Lombok Timur - Syahdan, Syahdan; Mulyani, Mulyani (ARZUSIN, 2022)
This research is entitled "The Role of Parents in Children's Learning Motivation at PAUD Salikussibyaan, Kelotok Hamlet, Wakan Village, Jerowaru District, East Lombok Regency". This study aims to determine the actions of parents in increasing children's learning motivation and to find out the obstacles faced by parents in increasing children's learning motivation in Salikussibyaan PAUD. This research is a descriptive qualitative research. The object of research is all parents of students whose children study at PAUD Salikussibyaan Kelotok which collected 54 people consisting of class A and class B. Data were obtained by observation, interview and documentation techniques. As for the data sources are parents of students who have children aged 5-6 years which is done with a sampling technique that is from the total population taken 10 people. Based on the research conducted, it was found that the role of parents in increasing children's learning motivation is still said to play an active role, in other words it is still relatively low because the motivation given by parents to children is only in matters of financing and words or advice, while children's daily lives still get less attention. from parents. Attention is still focused on the busyness of working every day both as laborers, farmers, employees and traders. In addition, parents also lack education and experience about the world of learning because on average they have a low educational background, from just elementary school graduates to those who have never received formal education at all.